Status Keberlanjutan Agroindustri Manisan Mangga di Kabupaten Cirebon - Anas Fitri Febriana; Trisna Insan Noor; Yosini Deliana (Universitas Galuh, 2026)
Mango fruit can be processed into various food products, either in unripe or ripe conditions, including candied mango, which has the potential to be developed as a value-added agroindustry. However, the development of the mango agroindustry in Cirebon Regency still faces several constraints, such as limited technological adoption, low access to financing, weak institutional support, and the dominance of non-formal small-scale enterprises. This study aims to analyze the sustainability status of the candied mango agroindustry in Cirebon Regency. The research employed a mixed-method approach involving nine candied mango agroindustry actors as respondents. Data analysis was conducted using the Multi-dimensional Scaling method through the Rap-Mango technique with the assistance of R software. The results indicate that the economic, ecological, and social dimensions are classified as less sustainable, while the institutional and technological dimensions fall into the unsustainable category. Overall, the candied mango agroindustry in Cirebon Regency is considered less sustainable, indicating the need for integrated strategic interventions, particularly in strengthening institutional capacity and technological adoption, to enhance the sustainability of the agroindustry in the future.